(Noble Gas)n‐NC+ Molecular Ions in Noble Gas Matrices: Matrix Infrared Spectra and Electronic Structure Calculations. Issue 5 (13th December 2021) - Tsegaw, Yetsedaw A.; Li, Hongmin; Andrews, Lester; Cho, Han‐Gook; Voßnacker, Patrick; Beckers, Helmut; Riedel, Sebastian
Abstract: An investigation of pulsed‐laser‐ablated Zn, Cd and Hg metal atom reactions with HCN under excess argon during co‐deposition with laser‐ablated Hg atoms from a dental amalgam target also provided Hg emissions capable of photoionization of the CN photo‐dissociation product. A new band at 1933.4 cm −1 in the region of the CN and CN + gas‐phase fundamental absorptions that appeared upon annealing the matrix to 20 K after sample deposition, and disappeared upon UV photolysis is assigned to (Ar) n CN +, our key finding. It is not possible to determine the n coefficient exactly, but structure calculations suggest that one, two, three or four argon atoms can solvate the CN + cation in an argon matrix with C−N absorptions calculated (B3LYP) to be between 2317.2 and 2319.8 cm −1 . Similar bands were observed in solid krypton at 1920.5, in solid xenon at 1935.4 and in solid neon at 1947.8 cm −1 . H 13 CN reagent gave an 1892.3 absorption with shift instead, and a 12/13 isotopic frequency ratio–nearly the same as found for 13 CN + itself in the gas phase and in the argon matrix. The CN + molecular ion serves as a useful infrared probe to examine Ng clusters. The following ion reactions are believed to occur here: the first step upon sample deposition is assisted by a focused pulsed YAG laser, and the second step occurs on sample annealing: (Ar)2 + +CN→Ar+CN + →(Ar) n CN + . Abstract : CCSD(T) calculated Ng−C−N + structures and observed frequencies . The bond lengths on top are in Å unit, the natural charges in blue below atoms, and the observed C−N stretching frequencies (cm −1 ) in a matrix of noble gas on right side. Reactions of laser ablated Zn, Cd, and Hg atoms with HCN have provided an opportunity to observe photoionization of CN, giving a new band at 1933.4 cm −1 in the region of CN and CN + gas phase fundamental absorptions. The absorption that appeared in annealing to 20 K and disappeared on UV photolysis has been assigned to (Ar)n CN + .